2005
DOI: 10.1093/cercor/bhj036
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Correlates of Cognitive Decline in Aging

Abstract: To explore neural correlates of cognitive decline in aging, we used longitudinal behavioral data to identify two groups of older adults (n = 40) that differed with regard to whether their performance on tests of episodic memory remained stable or declined over a decade. Analysis of structural and diffusion tensor imaging (DTI) revealed a heterogeneous set of differences associated with cognitive decline. Manual tracing of hippocampal volume showed significant reduction in those older adults with a declining me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
292
4
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(326 citation statements)
references
References 49 publications
26
292
4
4
Order By: Relevance
“…A longitudinal study 135 showed that both hippocampal volume and integrity of white matter in the corpus callosum were reduced in older adults and correlated with declining memory performance. Some studies 49,55 have found that age differences in activation within PFC were mediated by white matter integrity, such that more intact white matter was related to more activation, but others have failed to find this effect 94,136 .…”
Section: Brain Structurementioning
confidence: 99%
“…A longitudinal study 135 showed that both hippocampal volume and integrity of white matter in the corpus callosum were reduced in older adults and correlated with declining memory performance. Some studies 49,55 have found that age differences in activation within PFC were mediated by white matter integrity, such that more intact white matter was related to more activation, but others have failed to find this effect 94,136 .…”
Section: Brain Structurementioning
confidence: 99%
“…This analysis was conducted to determine whether age-related reductions in right MFG volume influenced the structure-function association within the right MFG and between the right MFG and other brain regions associated with episodic memory retrieval of faces in healthy adults. These include the bilateral occipitotemporal cortex, bilateral inferior parietal cortex, and ventrolateral PFC (VLPFC) (Rajah et al, , 2010Grady, 2002;Persson et al, 2006). To do this, we used the "Behavior/Seed" ST-PLS module (ST-BPLS) to identify patterns of whole-brain activity that covaried with right MFG volume (McIntosh et al, 2003).…”
Section: Fmri Analysis-correlating Brain Activity With Mfg Volumesmentioning
confidence: 99%
“…Hence, the reduced performance of the elderly in recency memory tasks could be related to reduced cortical thickness in frontal grey matter or to the disruption of white matter fiber tracts connecting frontal and posterior areas, both of which are frequently observed in healthy aging (e.g. [50,52,53]). …”
Section: Source and Item Memorymentioning
confidence: 99%